Testing slope homogeneity in large panels - Mohammad Hashem Pesaran; Takashi Yamagata (Center for Economic Studies and ifo Institute (CESifo), 2005)
This paper proposes a modified version of Swamy's test of slope homogeneity for panel data models where the cross section dimension (N) could be large relative to the time series dimension (T). The proposed test exploits the cross section dispersion of individual slopes weighted by their relative precision.
Keywords: C12; C33; 330; testing slope homogeneity; Hausman type tests; cross section dispersion tests; Monte Carlo results; PSID earnings dynamics; Panel; Statistischer Test